2012
DOI: 10.1002/chem.201103249
|View full text |Cite
|
Sign up to set email alerts
|

Creation of Chiral Thixotropic Gels through a Crown–Ammonium Interaction and their Application to a Memory‐Erasing Recycle System

Abstract: A unique class of oligothiophene-based organogelator bearing two crown ethers at both ends was synthesized. This compound could gelatinize several organic solvents, forming one-dimensional fibrous aggregates. From the observation of circular dichroism, it was confirmed that the helical handedness of the fibrous assembly is controllable by the chirality of 1,2-bisammonium guests, thus suggesting that one guest molecule bridges two gelator molecules through the crown-ammonium interaction. Interestingly, we have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(24 citation statements)
references
References 73 publications
0
24
0
Order By: Relevance
“…162 The helical one-dimensional assemblies were induced by the chirality of 1,2-bisammonium guests through host−guest interactions. It was interesting to note that the chirality of an oligothiophene-based organogel can be created by thermal gelation, whereas it was silent in thixotropic gelation.…”
Section: Chirality Transfer In Systems Containing Chiral and Achiral mentioning
confidence: 99%
“…162 The helical one-dimensional assemblies were induced by the chirality of 1,2-bisammonium guests through host−guest interactions. It was interesting to note that the chirality of an oligothiophene-based organogel can be created by thermal gelation, whereas it was silent in thixotropic gelation.…”
Section: Chirality Transfer In Systems Containing Chiral and Achiral mentioning
confidence: 99%
“…As the chiral auxiliary is from a "chiral pool" of amino alcohols 34 , a library of chiral supramolecular polymers can be readily formed. Before this work, there were only a few helical supramolecular polymer systems that can non-covalently accommodate various kinds of chiral auxiliaries from chiral pools 12,14,[19][20][21] . Our systematic studies revealed the clear relationship between the stereochemistry of the chiral auxiliaries, helical handedness of the polymers, and copolymerizability of the polymers.…”
Section: Discussionmentioning
confidence: 99%
“…Later, the scope of polymers was expanded to those with noncovalently formed backbones, the so-called "non-covalent polymers" or "supramolecular polymers", which opened up the new possibilities for polymer sciences [9][10][11][12][13][14][15][16][17] . Similar to covalent polymers, one-handed helicity of supramolecular polymers can be induced by the covalent 18 and non-covalent 14,[19][20][21] interactions of chiral small molecular units (Fig. 1a, iii).…”
mentioning
confidence: 99%
“…This selectivity of silica gel could be attributed individually to silylium ions [214]. However, the experimental variety of the ability to memorize structural information, which is characteristic of different gels, allows us to attribute this property to physical gels [215][216][217][218][219][220][221][222][223].…”
Section: Chiral Field (Chiral Memory) and Racemic Fieldmentioning
confidence: 99%